Changes in hydration status of elite Olympic class sailors in different climates and the effects of different fluid replacement beverages - Lewis, E. J.; Fraser, S. J.; Thomas, S. G.; Wells, G. D . (Journal of the International Society of Sports Nutrition, 2013)
Olympic class sailing poses physiological challenges similar to other endurance sports such as cycling or running, with sport specific challenges of limited access to nutrition and hydration during competition. As changes in hydration status can impair sports performance, examining fluid consumption patterns and fluid/electrolyte requirements of Olympic class sailors is necessary to develop specific recommendations for these elite athletes. The purpose of this study was to examine if Olympic class sailors could maintain hydration status with self-regulated fluid consumption in cold conditions and the effect of fixed fluid intake on hydration status in warm conditions.